Personnages obsédés et résistance du présent dans les romans de Kossi Efoui - Xavier Garnier (ReS Futurae)
Kossi Efoui’s novels are using a narrative device which is largely unexploited due to the solid relationship between narrative and past or future events : the hability to create characters linked to the present time by their own obsession. Cutting characters both from their heritage and their potentiality is a way to charge them with quite useful energy in postcolonial context. Sticking to the present brings about a political liberating force which doesn’t suppose to embrace a full and complete reality, since it has been destroyed by grotesque regime, but to stick to the abstraction of a fixed picture as ultimate resistance.